Towards Utilizing Flow Label IPv6 in Implicit Source Routing for Dynamic Source Routing (DSR) in Wireless Ad Hoc Network - Tai, Wai Yee; Tan, Chong Eng; Lau, Sei Ping (IEEE, 2012)
As Internet Protocol version 4 (IPv4) addresses deplete, Internet Protocol version 6 (IPv6) is introduced to alleviate the depletion with introduction of much needed functionality in security and so much more. Quality of Service (QoS) has been one of the aspects taken into consideration for improving network performance such as Packet Delivery Fraction (PDF), average End-to-end Delay and throughput. However in IPv4 network transmission, QoS is not given much attention as all transmission is treated equally with their “best-of-effort” services. Hence, in wireless ad hoc networks where unpredictable changes in topologies often disrupt on-going transmission. It will affect network performances with only the “best-of-effort” basis especially on real-time applications that require good network metrics. Therefore, in this paper we show how IPv6 can play its part in improving wireless ad hoc networks with QoS in Dynamic Source Routing (DSR) routing protocol.